2021
DOI: 10.20471/acc.2021.60.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Does the Type of Surgery in Brain Abscess Patients Influence the Outcome? Analysis Based on the Propensity Score Method

Abstract: SUMMARY There are different options for surgical treatment of brain abscess, mainly standard craniotomy and stereotactic aspiration. It has not yet been established which of these options is associated with a more favorable outcome under similar baseline conditions of patients. Demographic characteristics, microbiology, clinical presentation, and treatment outcome were analyzed for surgically treated adult patients with brain abscess over a 14-year period. A propensity score model was applied to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…In our literature research, we were able to find information on several of these aspects [24,[29][30][31], and medical textbooks are also rich with specific information that could be implemented in an automated generation of patient cases [19,20]. Our further literature research revealed that brain abscess, for instance, occurs more frequently in men (0.7/100.000) [34] and worse outcome is independently associated with Glasgow Coma Score on admission [35,36]. Hence, as an example, our generator could be expanded to determine gender as well, including a new Bernoulli experiment with the probability of success being 0.7 for male gender.…”
Section: Future Possibilitiesmentioning
confidence: 99%
“…In our literature research, we were able to find information on several of these aspects [24,[29][30][31], and medical textbooks are also rich with specific information that could be implemented in an automated generation of patient cases [19,20]. Our further literature research revealed that brain abscess, for instance, occurs more frequently in men (0.7/100.000) [34] and worse outcome is independently associated with Glasgow Coma Score on admission [35,36]. Hence, as an example, our generator could be expanded to determine gender as well, including a new Bernoulli experiment with the probability of success being 0.7 for male gender.…”
Section: Future Possibilitiesmentioning
confidence: 99%